Yielding pillar design in South African collieries - Oldroyd, Oldroyd (My University, 1997)
Three cases of pillar failure on Southern African Collieries have been studied to analyse the behaviour of both the pillars and the overlying strata. Each of the cases shows a different type ofpillar and strata behaviour during failure and thus provides an opportunity for back analysis. In the first case, pillars failed in a controlled fashion while the overlying strata behaved in an elastic fashion. In the second pillars failed in a controlled fashion while the surrounding strata behaved inelastically. In the third failure was initially controlled but became uncontrolled. Computer models have been run to determine the theoretical critical post peak pillar slopes and the results of these models have been compared with the actual pillar behaviour as derived from in-situ measurements during failure and that which might be predicted from the theory of controlled and uncontrolled pillar failure. Comparisons are also made with the expected behaviour implied from the results of in-situ strength tests carried out on small coal pillars to ascertain their load deformation characteristics. The results indicate that the behaviour of the pillars more closely resemble that predicted from in-situ tests carried out by Van Heerden4• The results also indicate inadequacies in using elastic methodologies to determine whether pillar failure will be controlled or uncontrolled.
A project report submitted to the Faculty of Engmeering, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Engineering.
Keywords: Coal mines and mining; Mining engineering; Barrier pillars; Rock mechanics; Coal mines and mining -- Safety measures; Coal mines and mining -- Data processing